Is Chelidonichthys lucerna (Linnaeus, 1758) a Marine Estuarine-Dependent Fish? Insights from Saccular Otolith Microchemistry - Ferreira, Inês; Daros, Felippe A. [UNESP]; Moreira, Cláudia; Feijó, Diana; Rocha, Alberto; Mendez-Vicente, Ana; Pisonero, Jorge; Correia, Alberto Teodorico (MDPI, 2023)
Tub gurnard, Chelidonichthys lucerna (Linnaeus, 1758), is a Mediterranean-Atlantic benthic species usually captured as by-catch by Portuguese traditional fisheries and considered the most important commercial fish species of the family Triglidae. However, to date, little is known about its habitat residency and whether the species can be considered a marine estuarine-dependent fish. Otolith microchemistry has proven effective in providing information about fish movement patterns throughout different water salinities. In this study, core-to-edge transects of Sr:Ca in the fish saccular otoliths of 35 juveniles of C. lucerna captured in March 2007 by a scientific survey along the Portuguese coast were used to assess the species movement between brackish and marine waters. Data suggest that most individuals (97%) have an estuarine-dependent profile, with 63% showing a clear presence in marine waters during the early life history periods. Evidence of an estuarine residence throughout the fish life cycle was found in only 3% of individuals. Ba:Ca profiles did not reflect an inverse relationship with Sr:Ca salinity results but corroborated findings from other authors about the influence of upwelling processes and freshwater runoffs on Ba incorporation into the otoliths of coastal fish. Furthermore, the data also showed that C. lucerna can occupy and migrate among habitats with diverse salinity degrees, showing high environmental plasticity and adaptation.
Keywords: Element:Ca; habitat residency; LA-ICP-MS; migratory behavior; sagitta; Triglidae